1973
DOI: 10.1113/jphysiol.1973.sp010154
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and the electrical activity of anoxic ventricular muscle

Abstract: SUMMARY1. The action potential duration of anoxic guinea-pig ventricular muscle was related to ATP generated by glycolysis. In 50 mm glucose medium the action potential duration was maintained; in 5 mm glucose medium the action potential duration shortened, the glycolytic rate declined and the ATP content was reduced.2. The action potential amplitude was related to the metabolic state of the muscle but not to the intracellular sodium concentration.3. It is suggested that changes in the action potential duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0
1

Year Published

1979
1979
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(53 citation statements)
references
References 42 publications
(49 reference statements)
8
44
0
1
Order By: Relevance
“…This is 2-5 times faster than the time needed to wash the drug out completely [ATP] in the submembrane pool than is present in the rest of the cytoplasm (Jones, 1986). The idea of functionally compartmentalized ATP is in line with the results of numerous groups, who have shown that it is preferentially glycolytic ATP which influences membrane proteins (McDonald & MacLeod, 1973;Bricknell, Daries & Opie, 1981;Hasin & Barry, 1984), including cardiac KATP channels (Weiss & Lamp, 1987. In our experiments…”
Section: Ik(atp) (Left Arrow) the Transient Appearance Of Ik(atp)supporting
confidence: 77%
“…This is 2-5 times faster than the time needed to wash the drug out completely [ATP] in the submembrane pool than is present in the rest of the cytoplasm (Jones, 1986). The idea of functionally compartmentalized ATP is in line with the results of numerous groups, who have shown that it is preferentially glycolytic ATP which influences membrane proteins (McDonald & MacLeod, 1973;Bricknell, Daries & Opie, 1981;Hasin & Barry, 1984), including cardiac KATP channels (Weiss & Lamp, 1987. In our experiments…”
Section: Ik(atp) (Left Arrow) the Transient Appearance Of Ik(atp)supporting
confidence: 77%
“…Although the exact mechanisms for the effects of glucose and insulin in the ischemic myocardium are not known, it seems reasonable to assume that they enhance membrane stability. 104,138 Shortly after, it was also observed that GIK decreases the infarct size after coronary artery ligation in dogs, lessens ultrastructural damage, and improves global contractile function of the heart. 139 The infusion of GIK was shown to reduce the frequency and duration of ventricular arrhythmias and to improve the survival of patients after myocardial infarction.…”
Section: Glucose and Insulin As Substrates For Postischemic Heartmentioning
confidence: 99%
“…45 Glycolysis during ischemia seems particularly important in providing a residual production of ATP. Such production sustains the activity of ATPrequiring enzymes, mainly the sarcolemmal Na ϩ ,K ϩ -ATPase 103,104 and the sarcoendoplasmic Ca 2ϩ -ATPase.…”
Section: Glycolytic Fluxmentioning
confidence: 99%
“…It is well known that there is a decline in both the amplitude and the duration of the cardiac action potential during ischaemia (Downar, Janse & Durrer, 1977;Russell, Smith & Oliver, 1979), and such changes could clearly reduce both Ca2+ influx across the plasmalemma and Ca2+ release from the sarcoplasmic reticulum. A similar mechanism is now well established under conditions of metabolic blockade (inhibition of both aerobic and anaerobic metabolism), when dramatic action potential shortening occurs (McDonald & MacLeod, 1973; Allen, Harris & Smith, 1987; Lederer, Nichols & Smith, 1989;Elliott, Smith & Allen, 1989), leading to a failure of Ca2+ release (Allen & Orchard, 1983) and therefore to mechanical failure (Stern, Silverman, Houser, Josephson, Capogrossi, Nichols, Lederer & Lakatta, 1988;Lederer et al 1989). …”
Section: I) Phi Fell Approximatelymentioning
confidence: 99%